ANALISIS SISTEM PENGENDALIAN INTERNAL PIUTANG DALAM MEMINIMALKAN PIUTANG TAK LANCAR PADA RUMAH SAKIT XYZ DI GRESIK - Anggita Lailatu Zalma; Wasti Reviandani (CV. ADIBA AISHA AMIRA, 2024)
This research discusses the analysis of the internal control system for receivables in minimizing non-current receivables at XYZ Hospital in Gresik. The purpose of this research is to find out and analyze the internal control system to minimize non-current receivables and the factors that influence non-current receivables at Insurance X at XYZ Hospital. The research method uses descriptive qualitative methods. Data analysis was carried out by means of observation and interviews. The results of this research show that the implementation of the internal control system for receivables is still less effective, as seen in the NPL calculation results from March 2023 - July 2023 of more than 12%, so it can be said that the risk profile level for non-current receivables at XYZ Hospital at Insurance X is within the criteria not healthy. Factors that influence receivables to become non-current are caused by internal and external factors